2009
DOI: 10.2298/tsci0904061m
|View full text |Cite
|
Sign up to set email alerts
|

Criteria selection for the assessment of Serbian lignites tendency to form deposits on power boilers heat transfer surfaces

Abstract: Based on investigations of ash deposit formation, semi-empirical indicators for slagging and fouling, based on ash chemical composition and its fusion temperature, have been determined. These criteria-indicators, in suggested limits, describe the coals on which they are based (North-American and British) well. However, the experience in the thermal power production sector of Serbia shows that their literal application to domestic coals does not produce satisfactory results. This contribution provides an analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
3
0
3
Order By: Relevance
“…Based on measured gamma-ray spectrum of 82 Due to low concentration of natural radio nuclides in lignite samples (approximately 3 times lower compared to values for subbituminous and bituminous coals) and obtained low correlation coefficient, integral or specific natural gamma radiation method could not be used for on-line measurement of ash content in Kolubara lignite. [12,13]. Based on results of these research and experimental verification of transmission radiation method/activity concentrations of naturally occurring radionuclides in the representative lignite samples from Kolubara basin, it could be concluded that the best method for on-line detection of lignite quality is based on Prompt gamma neutron activation method combined with transmission radiation method for detection of coal bed high at the transport belt and microwave method for moisture detection.…”
Section: Physical-chemical Properties Of Coalmentioning
confidence: 92%
“…Based on measured gamma-ray spectrum of 82 Due to low concentration of natural radio nuclides in lignite samples (approximately 3 times lower compared to values for subbituminous and bituminous coals) and obtained low correlation coefficient, integral or specific natural gamma radiation method could not be used for on-line measurement of ash content in Kolubara lignite. [12,13]. Based on results of these research and experimental verification of transmission radiation method/activity concentrations of naturally occurring radionuclides in the representative lignite samples from Kolubara basin, it could be concluded that the best method for on-line detection of lignite quality is based on Prompt gamma neutron activation method combined with transmission radiation method for detection of coal bed high at the transport belt and microwave method for moisture detection.…”
Section: Physical-chemical Properties Of Coalmentioning
confidence: 92%
“…Na osnovu obimne baze podataka sakupljene za domaće ugljeve i korelativne analize postojećih polu-empirijskih kriterijuma razvijeni su pokazatelji (indikatori) tendencije pepela goriva za stvaranje naslaga na grejnim površinama. Ključne empirijske korelacije razvijene kod nas su (Repić, 1979, Mladenović, 2005, Mladenović et al 2009): a) Interval između početne deformacije (t1) i temperature topljenja pepela (t4). Ako je interval mali, tanak, tečni sloj šljake biće formiran na zidovima ložišta i njega je izuzetno teško kontrolisati pomoću duvača čađi.…”
Section: Rezultati I Diskusijaunclassified
“…Ovi indikatori (Tabela 1) mogu se definisati kao (Repić, 1979, Pronobis, 2005 Indeks aglomeracije fluidizovanog sloja: BAI = Fe2O3)/(Na2O + K2O). Korelaciona analiza testiranih domaćih goriva dala je tačnu funkcionalnu zavisnost kriterijuma B, B/A, It i So (Repić, 1979, Mladenović et al 2009). Granice za primenu ovih kriterijuma su u skladu sa time i stoga se bilo koji od ovih četiri kriterijuma može koristiti za procenu tendencije lepljenja pepela domaćih lignita (Tabela 1).…”
Section: Rezultati I Diskusijaunclassified
“…It has been estimated to be an important source of losses of availability and energy efficiency in thermal power plants, that may amount to 1% under normal operating conditions [1]. A large number of case studies can be found in recent decades [3][4][5], indicating a continuous worldwide interest in this problem. The collected data showed 7% of units suffering from frequent fouling and 40% reporting occasional problems, out of a total of 91 pulverized-coal utility boilers in the USA.…”
Section: Introductionmentioning
confidence: 99%